Characterization of Xanthomonas euvesicatoria Strains Pathogens of Pepper in Serbia - Maja Ignjatov (Pesticidi i Fitomedicina, 2010)
During spring and summer of 2008, 101 bacterial strains was isolated from the diseasedpepper leaves collected from different pepper growing areas in the Republic of Serbia. Theaim of this research was to characterize the isolated strains and determine their taxonomicposition according to the most recent nomenclature.Pathogenic, biochemical and physiological characteristics of isolated bacteria weretested using standard bacteriological tests. The pathogen races were determined accordingto the reaction of differential varieties of Early Calwonder (ECW), their isogenic lines(ECW-10R, ECW-20R, ECW-30R) and Capsicum pubescens. The sensitivity of strains to bactericideswas studied in vitro by culturing bacteria on sucrose pepton agar (SPA) plates, amendedwith filter-sterilized aqueous solution of streptomycin and kasugamycin (50, 100, 200ppm) or copper-sulphate (100, 200 ppm).Based on pathogenic, biochemical and physiological characteristics, the investigatedstrains belonged to Xanthomonas euvesicatoria. The reaction of pepper differential varietiesindicated that these strains belonged to pepper races P1, P3, P7, P8. Streptomycin resistantstrains were not detected, but 6 strains were resistant to kasugamycin (50 ppm) and 13strains to copper-sulphate (200 ppm), indicating bacterial resistance development.